The Association Between Environmental Perchlorate, Nitrate, and Thiocyanate Exposure and Oral Pain in NHANES - Yu, Jintao; Guo, Jiawen; Zhang, Hengguo; Cheng, Xu (Frontiers in Public Health, 2022)
Aim: To examine the human exposure to perchlorate, nitrate and thiocyanate and their associations with oral pain (OP) in general population from U.S.. Methods: A total of 13,554 participants were enrolled from the National Health and Nutrition Examination Survey. Urinary perchlorate, nitrate and thiocyanate were measured using ion chromatography coupled with electrospray tandem mass spectrometry. Multivariable linear and logistic regressions were performed to explore the associations of urinary perchlorate, nitrate and thiocyanate with the prevalence of oral pain. Restricted cubic splines were used to explore the nonlinearity. Results: There are 3129 OP cases. There were higher urinary level of perchlorate, nitrate and thiocyanate in OP. We found that urinary thiocyanate was positively associated with OP (odds ratio [OR] 1.06; [1.00, 1.13]; p=0.049). Restricted cubic spines reveled that urinary thiocyanate was U-shaped associated with OP. Conclusions: Urinary thiocyanate was U-shaped associated with OP, suggesting that we should keep the exposure of thiocyanate under a reasonable range.